The Relationship Between Leadership And Teachers' Performance At State Vocational High SchoolL “X” Bandung - Eka Sari Budihastuti; Arif Yusuf Hamali (Bina Nusantara University, 2016)
This research was conducted at State Vocational High School “X” Bandung, aimed to determine the relationship of leadership and teachers’ performance, and also to analyze the effect of leadership on teachers’ performance at State Vocational High School “X” Bandung. Respondents of this research are 30 employees selected by census technique. This research uses descriptive and associative method, which tests the connection using the Spearman Rank correlation analysis, and also done to determine the accuracy of measurement using by the validity and reliability test. Results of the validity and reliability test of variables X and Y are valid and reliable. Calculations were performed using SPSS software version 19. The result of this study shows that leadership is in the category of good and teachers’ performance is also in the category of good. Results shows the correlation of leadership with teachers’ performace at State Vocational High School “X” Bandung based on the interpretation of Pearson Product Moment correlation is in the criteria of strong. It shows that thehypothesis is proved, there is significant relationship between leadership and teachers’ performance at State Vocational High School “X” Bandung.